(3GdLhGgQ GdecddI def QGe GdWQb GdecedI aj GdbQGAGJ GdYTQs - (3GdYhaj, eMeO Hf CMeO, J (B1050 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj gOGfG dJdGhI cJGHg hHYO ajbhd eMeO Hf GMeO GdYhaj GNJUQJ cJGHj GdeSei HMQ GdeYGfj hSejJg GdLhGgQ GdecddI def QGe GdWQb GdecedI s
(3BNQgG (B:s
(3hajgG eMPhaI hgj GdLhGQ aj GdHMQ CKHJgG aj GdhUd hbQC fGaY hCHh LYaQ hCHh YeQh haj GdMGdjf GHf cKjQ hjYbhH hGddg GYdes
(3aj BNQg fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 9s
(3eYLe GdeDdajf (B3 / 89s
(3gOjI GdYGQajf (B2/ 263s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs